Greek Film Noir - Agathos, Thanassis; Aitaki, Georgia; Broe, Dennis; Chairetis, Spyridon; Chalkou, Maria; Chen, Yun-hua; Constandinides, Costas; Fessas, Nikitas; Karalis, Vrasidas; Mermigka, Ioulia; Poulakis, Nick; Poupou, Anna; et al. (Edinburgh : Edinburgh University Press, 2022)
Investigates how film noir has been received, adapted and developed in Greece, from the 1940s to the presentTraces the evolution of a scholarly neglected - in the Greek context - film genre; it introduces an original corpus of texts extending from the 1940s to the present Offers a panoramic overview of leading Greek auteur figures, from Nikos Koundouros and Tonia Marketaki to Theo Angelopoulos and Nikos Nikolaidis, viewing their work, for the first time, from a film-noir stylistic and thematic perspectivePresents the cultural context of a noir universe in post-WWII Greece, including: pulp fiction and crime literature, jazz and pop music, media discourses, Greek commercial cinema's advertising and promotional strategiesExplores the historical representations and ideological debates reflected in the Greek film noir in the aftermath of WWII and the Greek Civil War and traces the political re-appropriation of the genre by the left-wing filmmakers of New Greek Cinema during the military junta (1967-1974) Explains the reasons behind the post-2009 crisis revival of the noir genre in contemporary Greek cinema and the Greek Weird WaveConfirms noir's particular tendency to transcend boundaries as it spills out onto other genres, producing innovative hybrids; and its ability to express the gender and socio-political anxieties of its eraPresents an argument for the transnational character of the noir phenomenon and the complex relationship of European cinemas with HollywoodOffering the first comprehensive study of Greek film noir, this book explores the reception and influence of U.S. and European film noir and neo-noir in Greece and their effect on Greek filmmaking. Employing theoretical frameworks from New Film History, it offers a fresh look at underrated or neglected cultural products to provide insights into Greek modernity and reveal the affinities of established Greek auteurs with the film-noir tradition. Firmly establishing Greece on the film noir cinematic map, it provides a panoramic overview of leading Greek auteurs, from Nikos Koundouros and Maria Plyta to Theo Angelopoulos and Nikos Nikolaidis, whose work is innovatively viewed from an angle of film-noir style and thematics.
Frontmatter -- CONTENTS -- List of Figures -- Acknowledgements -- Contributors -- Traditions in World Cinema -- Foreword -- Introduction -- PART I. PARTNERS IN CRIME: RECEPTIONS, AFFINITIES, HYBRIDITIES -- 1 There Will Be Ogres: The Interstitial Aesthetics of Film Noir in the Early Films of Nikos Koundouros -- 2 Of Mice, Men and Greek Film Noir: The Little Mouse -- 3 Historical Coincidence or Generic Cross-Pollination? The Angry Hills and the Birth of Film Noir in Greece -- 4 Noir Backstage: Yannis Maris from Page to Screen -- 5 Dark Cinema, Dark Sounds: Mimis Plessas and the Integration of Jazz into Greek Film Noir -- 6 Fatal Absences and Female Gazes: Alternative Femininities in Greek Film Noir and the Psychological Thriller -- 7 Bums and Dark Alleys: Constructing Queerness in a Mid-1960s Greek Noir -- PART II. POLITICAL ASPECTS AND TRANSNATIONAL DYNAMICS OF THE GREEK NEO-NOIR -- 8 A Dark Intrigue of Murder: Kierion and Reconstruction, or Film Noir as Politics -- 9 Neo-Noir and 'Becoming-Murderer' in Tonia Marketaki's John the Violent -- 10 The Unbearable Queerness of Singapore Sling: Towards a Queer Ethics and Politics of Irony -- 11 Hong Kong and Athens: Contested Spaces of the Global and the Local in the Neo-Noir of John Woo and Alexis Alexiou -- 12 Darker Worlds Come in Small Packages: Neo-Noir Sensibility in Greek Cypriot Short Films -- 13 Greek Sleuths and Tough Cops: Noir Masculinities in Television Crime Shows (1992-2020) -- 14 Mediterranean Film Noir: Twilight Falls on mare nostrum -- Appendix: Greek Films and Television Series/Shows Featuring Dominant Noir or Neo-Noir Tropes -- Index
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 30. Aug 2022).
JSTOR
Keywords: Motion pictures -- Greece -- History; Film, Media & Cultural Studies; Cinéma -- Grèce -- Histoire; PERFORMING ARTS / Film & Video / Direction & Production; LITERARY CRITICISM / General; Motion pictures; Greece; Films, cinema; Film history, theory & criticism; Film: styles & genres; Performing Arts; History